Предмет: Математика,
автор: Sofiawashington
Выполните действия:
А)(2 корень 11 +3)(2 корень 11 -3)
Б)(2 корень 3 + корень 2)^2-4 корень 6
Ответы
Автор ответа:
0
(2√11+3)(2√11-3)=(2√11)²-3²=4*11-9=44-9=35
(2√3+√2)²-4√6=((2√3)²+2*2√3*√2+(√2)²)-4√6=12+4√6+2-4√6=14
(2√3+√2)²-4√6=((2√3)²+2*2√3*√2+(√2)²)-4√6=12+4√6+2-4√6=14
Автор ответа:
0
Спасибо)
Похожие вопросы
Предмет: Математика,
автор: saizhan1981
Предмет: Математика,
автор: polinakostina312
Предмет: Информатика,
автор: mikan1tsumiki
Предмет: Математика,
автор: webdesign73